Dialytic management of inborn errors of metabolism - Schaefer, Franz; Daschner, Markus (Pediatric dialysis, 2004)
Metabolic crises in children with inborn errors of metabolism are caused by the accumulation of neurotoxic metabolites. Rapid elimination of these metabolites is crucial to prevent irreversible neuronal damage since long-term outcome is correlated with the duration of the metabolic crisis. This chapter reviews the principles of dietetic, pharmacological and dialytic management of neonatal metabolic emergencies.
Gesehen am 29.01.2021